Game as a Way to Enhance Students’ Cognitive Activity - E. F. Gladkaya (Высшее образование в России)
The article deals with the description and analysis of the teaching experience of enhanc-ing students’ cognitive activity through intellectual games-competitions (games in pairs, teamwork) in the framework of Humanities “Russian language and speech culture” and “Rhetoric” at technical University. Special attention is paid to the description of the technology of games, pedagogical nuances that must be considered by a teacher to achieve maximum results of educational and gaming activities. On the basis of the described experience, conclusions are drawn about the rich possibilities of using games-competitions in the educational process of higher school. Properly organized game allows to create a favorable for learning emotional background and establish psychological contact between all participants of communication. In the game situation, the emotional and intellectual forces of students are mobilized. The group work develops communication and teamwork skills and the ability to achieve mutual understanding, to get the value of each member of the group. An important advantage of the game forms is that they can be used at all stages of training: from the introduction of new material to the control of acquired knowledge and skills. The emotions experienced during the game by students, increase responsibility for the result, contribute to better learning of educational material, which is confirmed by the control tests.